Postfire growth of seeded and planted big sagebrush—strategic designs for restoring greater sage‐grouse nesting habitat. Issue 6 (22nd September 2020) - Pyke, David A.; Shriver, Robert K.; Arkle, Robert S.; Pilliod, David S.; Aldridge, Cameron L.; Coates, Peter S.; Germino, Matthew J.; Heinrichs, Julie A.; Ricca, Mark A.; Shaff, Scott E.
Abstract : Wildfires change plant community structure and impact wildlife habitat and population dynamics. Recent wildfire‐induced losses of big sagebrush ( Artemisia tridentata ) in North American shrublands are outpacing natural recovery and leading to substantial losses in habitat for sagebrush‐obligate species such as greater sage‐grouse. Managers are considering restoration strategies that include planting container‐grown sagebrush to improve establishment within areas using more conventional seeding methods. Although it is thought that planting sagebrush provides initial structural advantages over seeding, empirical comparisons of sagebrush growth are lacking between individuals established postfire using both methods. Using a Bayesian hierarchical approach, we evaluated sagebrush height and canopy area growth rates for plants established in 26 seeded and 20 planted locations within the Great Basin. We then related recovery rates to previously published nesting habitat requirements for sage‐grouse. Under average weather conditions, planted or seeded sagebrush will require 3 or 4 years, respectively, and a relatively high density (≥2 plants/m 2 ) to achieve the minimum recommended canopy cover for sage‐grouse (15%). Sagebrush grown in warmer and drier conditions met this cover goal months earlier. Although planted sagebrush reached heights to meet sage‐grouse nesting requirements (30 cm) 1 year earlier than seeded plants, seeded individuals were approximately 19 cm taller with 410 cm 2 more canopy area than planted sagebrush after 8 years. However, big sagebrush establishment from seed is unreliable. Strategically planting small, high‐density patches of container‐grown sagebrush in historic sage‐grouse nesting habitat combined with lower density seedings in larger surrounding areas may accelerate sage‐grouse habitat restoration.